The sense of semblance : philosophical analyses of Holocaust art - Pickford, Henry W. (UPCC book collections on Project MUSE., 2013)
"Drawing on work in contemporary analytic philosophy and Adorno's normative aesthetic theory, this book aims to show how selected Holocaust artworks in a variety of media (lyric poetry by Paul Celan, Holocaust memorials, quotational texts by Heimrad Bc̃ker, Claude Lanzmann's film Shoah and Art Spiegelman's graphic novel Maus) fulfill both aesthetic and historical requirements of the genre"--